THE EFFECT OF FINISHED GOODS INVENTORY ACCOUNTING INFORMATION SYSTEM ON FINISHED GOODS INVENTORY INTERN CONTROL AT A TEXTILE COMPANY IN THE CITY OF BANDUNG - Kiki Yanuar; Boy Suzanto; Dhea Perdana Coenraad; Titi Titi; Annita Jannah (Jurnal Computech & Bisnis (e-Journal), 2022)
The implementation of the research took place at one of the textile companies in the city of Bandung. The research method used in this study is a quantitative research method with a descriptive method approach and a verification method (correlation coefficient, simple regression, coefficient of determination). The population in this study amounted to 30 people.The results showed that the Finished Goods Inventory Accounting Information System was in the pretty good category with a score of 3.24, and the Internal Control of Finished Goods Inventory was in the pretty good category with a score of 3.18.The results of calculating the independent variable, namely the Finished Goods Inventory Accounting Information System, At the same time, the dependent variable is the Finished Goods Inventory Internal Control. Therefore, this study has a strong correlation because it shows the results of calculating the correlation coefficient, which has a value of r = 0.862. Furthermore, simple linear regression that is Y = 1.909 + 0.890 X. Therefore, the coefficient of determination (R2) expressed as a percentage illustrates the magnitude of the effect of the accounting information system on ready-to-use goods inventory (x) on Finished Goods Inventory internal control (y) of 0.744 or 74.4%. The remaining 25 are the influence of other factors that the authors did not examine in this study.Keywords: Finished Goods Inventory Accounting Information System and Finished Goods Inventory Internal Control.